Acute Mediastinal Bleeding with Pleural Escape: Case Report of a Rare Interventional Complication with Unusual Resolve - Widodo, Wishnu Aditya; Mansjoer, Arif; Dilawar, Ismail; Kurnia, Andri; Ruslim, Daniel (International Journal of Angiology, 2022)
Acute mediastinal bleeding is a very rare complication of cardiac intervention. It is a life-threatening situation when this condition causes acute compression of the mediastinal area. A 59-year-old man was diagnosed with inferior ST-elevation myocardial infarction with ongoing chest pain and underwent an urgent percutaneous coronary intervention procedure. After coronary stent was implanted, patient complained of chest tightness, and suffocation, blood pressure dropped, O2 saturation dropped, and was difficultly intubated. Image acquisition by C-arm showed a large bulging in aortic arch area. Contrast-enhanced computed tomography ruled out aortic dissection, but noted a large mediastinal mass that was radiated to the neck. The bulging was spontaneously regressed, and a large left pleural effusion was developed. Left pleural tapping was performed on day 7, and a total of 1.5-L hemorrhagic fluid was evacuated. In our case, unusual drainage from mediastinal to pleural space has probably save the patient.
Keywords: acute mediastinal bleeding; acute mediastinal compression; pleural escape; rare complication; percutaneous coronary intervention; ST-elevation myocardial infarction; life-threatening